KAPASITAS ADSORBSI LOGAM KROMIUM (VI) DENGAN ADSORBEN PEKTIN DARI KULIT LEMON - Mardhiyah Nadir; Yuli Patmawati; Aditya Alexander (Politeknik Negeri Samarinda, 2021)
Chromium is a heavy metal that can pollute the aquatic environment. Tackling water pollution can be done by using the adsorption method using pectin from lemon peel. This study aims to determine the adsorption equation of chromium (VI) with pectin adsorbent from lemon peel and to determine the effect of adsorbent mass on chromium (VI) metal uptake. The lemon peel was extracted with a mass of 15 grams using the help of Microwave Assisted Extraction (MAE) with an extraction time of 26 minutes using 300 Watt power. The adsorption process was carried out with mass variations (1.2 gr; 1.3 gr; 1.4 gr; 1.5 gr and 1.6 gr) with a contact time of 1 hour and a stirring speed of 250 rpm. The analytical method used to measure the adsorption value is Atomic Absorption Spectrophotometry (AAS). The Cr (VI) adsorption equation follows the Langmuir equation. The results of this study indicate that the optimum conditions for adsorption, namely the pectin mass of 1.5 g, can reduce Cr(VI) levels by 0.0452 mg / g (70.23%).